(untitled) (Research, Society and Development, 2021)
The brazilian public health was constituted from countless historical factors and counted with the popular participation for its consolidation, a process that opened spaces for popular manifestation on the Unified Health System (SUS) management. These spaces are called social control organs, are laid out in law and have a big importance for the development of public policy that attend to the real needs of citizens. The present article aims to understand the engagement and knowledge of people residing in a city in Rio Grande do Sul about the local Municipal Health Council (CMS). It is a qualitative study, descriptive, in which it was made an experience report referent an activity about social control realized in a Public Health class, from which two student from the courses of psychology and physiotherapy elaborated a survey to consult the population about their knowledge about the organ. The survey was made in a Google platform and applied with SUS users in december 2020. The results point that the population, in fact, do not know the CMS and, consequently, does not effectively exercise its rights. It is understood that the social participation is a relatively recent process in the history of the country and it is in construction process. However, for the popularization of social control to occur, it is necessary to expend efforts, inform the population and encourage their participation.